2014
DOI: 10.1111/bjh.13245
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II study exploring ImMucin, a pan‐major histocompatibility complex, anti‐MUC1 signal peptide vaccine, in multiple myeloma patients

Abstract: Summary ImMucin, a 21‐mer cancer vaccine encoding the signal peptide domain of the MUC1 tumour‐associated antigen, possesses a high density of T‐ and B‐cell epitopes but preserves MUC1 specificity. This phase I/II study assessed the safety, immunity and clinical response to 6 or 12 bi‐weekly intradermal ImMucin vaccines, co‐administered with human granulocyte‐macrophage colony‐stimulating factor to 15 MUC1‐positive multiple myeloma (MM) patients, with residual or biochemically progressive disease following aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 40 publications
1
36
0
Order By: Relevance
“…52 Likewise, injection of naked peptides without adjuvant has typically been shown to be minimally immunogenic; and co-administration with immunologic adjuvants is typically required to induce detectable T-cell or B-cell responses. 52 However, in vitro and in vivo results with MUC1's TAA 45,48 and MTb-derived 43,46 SP domains, somewhat deviated from the general observations. SP domains directly activated in vitro proliferation of PBMC samples isolated from na€ ıve donors.…”
Section: Generation Of Humoral Immunitymentioning
confidence: 70%
See 4 more Smart Citations
“…52 Likewise, injection of naked peptides without adjuvant has typically been shown to be minimally immunogenic; and co-administration with immunologic adjuvants is typically required to induce detectable T-cell or B-cell responses. 52 However, in vitro and in vivo results with MUC1's TAA 45,48 and MTb-derived 43,46 SP domains, somewhat deviated from the general observations. SP domains directly activated in vitro proliferation of PBMC samples isolated from na€ ıve donors.…”
Section: Generation Of Humoral Immunitymentioning
confidence: 70%
“…46 Similarly, these SP domains induced a strong and specific cellular immune response [45][46][47] and anti-tumor activity 45 in both mice and in a firstin-human study. 48 More recently, an additional support for the potency of SP domains was published by Kerzerho et al, which demonstrated the existence of multiple CD4…”
Section: Antigen-specific Cd4mentioning
confidence: 90%
See 3 more Smart Citations